Aetiology of acute respiratory infection in preschool children requiring hospitalisation in Europe—results from the PED-MERMAIDS multicentre case–control study. Issue 1 (29th July 2021) - Kohns Vasconcelos, Malte; Loens, Katherine; Sigfrid, Louise; Iosifidis, Elias; Epalza, Cristina; Donà, Daniele; Matheeussen, Veerle; Papachristou, Savvas; Roilides, Emmanuel; Gijon, Manuel; Rojo, Pablo; Minotti, Chiara; et al.
Abstract : Background: Both pathogenic bacteria and viruses are frequently detected in the nasopharynx (NP) of children in the absence of acute respiratory infection (ARI) symptoms. The aim of this study was to estimate the aetiological fractions for ARI hospitalisation in children for respiratory syncytial virus (RSV) and influenza virus and to determine whether detection of specific respiratory pathogens on NP samples was associated with ARI hospitalisation. Methods: 349 children up to 5 years of age hospitalised for ARI (following a symptom-based case definition) and 306 hospital controls were prospectively enrolled in 16 centres across seven European Union countries between 2016 and 2019. Admission day NP swabs were analysed by multiplex PCR for 25 targets. Results: RSV was the leading single cause of ARI hospitalisations, with an overall population attributable fraction (PAF) of 33.4% and high seasonality as well as preponderance in younger children. Detection of RSV on NP swabs was strongly associated with ARI hospitalisation (OR adjusted for age and season: 20.6, 95% CI: 9.4 to 45.3). Detection of three other viral pathogens showed strong associations with ARI hospitalisation: influenza viruses had an adjusted OR of 6.1 (95% CI: 2.5 to 14.9), parainfluenza viruses (PIVs) an adjusted OR of 4.6 (95% CI: 1.8 to 11.3) and metapneumoviruses an adjusted OR of 4.5 (95% CI: 1.3 to 16.1). Influenza viruses had a PAF of 7.9%, PIVs of 6.5% and metapneumoviruses of 3.0%. In contrast, most other pathogens were found in similar proportions in cases and controls, including Streptococcus pneumoniae, which was weakly associated with case status, and endemic coronaviruses. Conclusion: RSV is the predominant cause of ARI hospitalisations in young children in Europe and its detection, as well as detection of influenza virus, PIV or metapneumovirus, on NP swabs can establish aetiology with high probability. PAFs for RSV and influenza virus are highly seasonal and age dependent.